Problems of Mathematical Problem Solving for Grade VIII Students in Circle Material - Triyana, Evi; Kusno, Kusno (Postulat : Jurnal Inovasi Pendidikan Matematika, 2025)
The ability to solve mathematical problems is one of the main competencies that need to be mastered in mathematics learning. However, a number of studies reveal that students still experience obstacles in solving math problems, especially on the topic of circles. The purpose of this study is to explore the various causes of difficulties of grade VIII students in solving mathematical problems related to circle material and offer alternative solutions that can be used in the learning process. This research was conducted with a descriptive qualitative approach through a case study of several junior high school students in grade VIII. The findings of this study show that the main obstacles for students lie in the lack of understanding of the basic concept of circles, errors in the use of formulas, and limitations in designing problem-solving steps. Therefore, problem-based learning strategies and contextual learning approaches are recommended to be implemented to support improved student understanding.